Morphology and phylogeny of Halamphora yongxingensis sp. nov. (Bacillariophyta), a new marine benthic diatom isolated from Yongxing Island, South China Sea - Jiang, Hai-Ying; Hu, Chao-Qun; Yang, Hai-Peng; Zhang, Lv-Ping; Peng, Peng-Fei; Luo, Peng; Zhao, Zhe; Xia, Jian-Jun (Phytotaxa, 2015)
Halamphora yongxingensis sp. nov., a marine benthic diatom isolated from an intertidal reef around the Yongxing Island, South China Sea (16° 58’ 43.3” N, 112° 14’ 41.7” E), is described in this study on the basis of light and electron microscopy. This diatom is also compared with related taxa such as Halamphora subturgida (Hustedt) Levkov and Amphora subtropica Wachnicka & Gaiser. In addition, phylogenetic analyses based on 18S rDNA and rbcL gene were also conducted. The results revealed that H. yongxingensis was clustered into the Halamphora clade, closely related to Halamphora montana (Krasske) Levkov. We discuss morphological differences between H. yongxingensis and H. montana.